Not all cities are alike: House price heterogeneity and the design of macro-prudential policies in China - Michael Funke; Andrew Tsang; Linxu Zhu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
This paper investigates the implementation of regionally differentiated macro-prudential policies in China. To assess the relative intensity of the city-level macro-prudential policies over time, we construct a time-varying city-level macro-prudential policy intensity indicator for 70 Chinese cities from 2010-2017. The empirical evidence shows China's macro-prudential toolbox has gradually evolved toward city-level policies tailored to granular local conditions to mitigate risks.
URN:NBN:fi:bof-201811142128
Keywords: O18; E52; C38; 330